Chronic exposure to UVB radiation and 4-tert-octylphenol disrupts metamorphosis and the thyroid system of northern leopard frog (Rana pipiens) tadpoles - Croteau, Maxine Carmen (University of Ottawa (Canada), 2009)
Ultraviolet B radiation (UVBR) and chemical pollutants are environmental stressors that may affect amphibian populations. While adverse effects of UVBR and chemicals on amphibians are documented, few studies examined the effects of interactions between stressors on amphibian health. Gosner stage 25 Rana pipiers tadpoles were chronically exposed to environmentally relevant levels of UVBR (0.15-0.22 W/m2) and the estrogenic chemical 4-tert-octylphenol (OP) (0.01 nM or 10 nM) alone and in combination. Tadpoles exposed to UVBR and/or OP exhibited significantly delayed development at stage 29. Significantly fewer UVBR-treated tadpoles developed past stage 34 and metamorphosed. Effects of UVBR/OP on the thyroid system were assessed because it is the main regulator of amphibian metamorphosis. Stage 29 and 34 tadpoles were collected for gene expression analysis in tail and T3 (triiodothyronine) whole body levels (minus tail). Moreover, we examined whether pre-exposure to UVBR/OP affected the molecular and morphological responses of tadpoles to exogenous T3. OP increased the expression of several genes in tail and brain and/or their response to T3 (e.g., deiodinase 2), and the addition of UVBR can alter the effect of OP. Although UVBR had no observable effect on gene expression, developmentally delayed UVBR-treated stage 31 tadpoles exposed to T3 exhibited slowed tail resorption and accelerated hind limb development. UVBR and/or OP did not affect T3 levels of stage 29 and 34 tadpoles. However, a decrease and increase in deiodinase 2 and 3 (D2 and D3) mRNA levels, respectively, were observed in groups of tadpoles with slowed developmental rates at those stages. Since D2 activates and D3 inactivates thyroid hormones (TH), UVBR/OP mediated disruptions in development are likely caused by dysfunctions in the localized metabolism of THs. These results indicate that environmental levels of UVBR and/or OP can affect metamorphosis, potentially by disrupting the biological action of T3 and deiodinases in peripheral tissues, which could contribute to population declines.
Keywords: Biology, Evolution and Development.; Environmental Health.